Investigation into the semiochemical communication involved in neonatal offspring recognition in sheep - Viviers, Marlize Zaretha (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD (Chemistry and Polymer Science))--University of Stellenbosch, 2010.